Answers

The Brainliest Answer!
2016-02-17T19:24:17+05:30
(1) x²-6x+8
=> x²-2x-4x+8
=> x(x-2)-4(x-2)
=> (x-4)(x-2)

Area of rectangle = length*breadth
where length > breadth
L*B = (x-4)(x-2)
∴ length = (x-2) units
∴ breadth = (x-4) units

Similarly,

(2)
length = (x-1) units
breadth = (x-2) units

(3)
length = (x-2) units
breadth = (x-5) units

(4)
length = (x+20) units
breadth = (x-1) units

(5)
length = (x+5) units
breadth = (x+4) units
4 5 4
means  it is applicable to every equation given
Yep